2012
DOI: 10.1371/journal.pone.0046200
|View full text |Cite
|
Sign up to set email alerts
|

MRI-Based Volumetry Correlates of Autobiographical Memory in Alzheimer's Disease

Abstract: The aim of the present volumetric study was to explore the neuro-anatomical correlates of autobiographical memory loss in Alzheimer's patients and healthy elderly, in terms of the delay of retention, with a particular interest in the medial temporal lobe structures. Fifteen patients in early stages of the disease and 11 matched control subjects were included in the study. To assess autobiographical memory and the effect of the retention delay, a modified version of the Crovitz test was used according to five p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 82 publications
(162 reference statements)
3
26
0
Order By: Relevance
“…Interestingly, a study has found associations between hippocampal volume and episodic autobiographical memory in AD for both recent and remote memories (Philippi et al, 2012). In contrast, a functional MRI study has demonstrated that retrieval of recent memories in AD participants was more associated with right prefrontal activation whereas retrieval of remote memories was more associated with left prefrontal activation, regardless of hippocampal activation (Eustache et al, 2004).…”
Section: Cognitive and Neuroanatomical Underpinnings Of Autobiogramentioning
confidence: 99%
“…Interestingly, a study has found associations between hippocampal volume and episodic autobiographical memory in AD for both recent and remote memories (Philippi et al, 2012). In contrast, a functional MRI study has demonstrated that retrieval of recent memories in AD participants was more associated with right prefrontal activation whereas retrieval of remote memories was more associated with left prefrontal activation, regardless of hippocampal activation (Eustache et al, 2004).…”
Section: Cognitive and Neuroanatomical Underpinnings Of Autobiogramentioning
confidence: 99%
“…Studies about autobiographical memory in cognitive impairment are consensual on the fact that the progression of dementia involves decline in autobiographical memory (Addis & Tippett, 2004;El Haj, Postal, Le Gall, & Allain, 2011;Irish et al, 2011;Martinelli, Anssens, Sperduti, & Piolino, 2013;Muller et al, 2012;Philippi et al, 2012) and that these changes can be observed from early stages (Lalanne, Gallarda, & Piolino, 2014;Lemos, Hazin, & Falcão, 2012), resulting in a loss of personal identity (Lalanne et al, 2014). Some particularities are nevertheless to be highlighted in this process.…”
Section: Reminiscence and Autobiographical Memorymentioning
confidence: 99%
“…Some particularities are nevertheless to be highlighted in this process. Firstly, studies observed a phenomenon entitled "positive temporal gradient" (a decrease in autobiographical memories for the recent past events), associated to a characteristic of Alzheimer's disease: the presence of retrograde amnesia (Muller et al, 2012;Philippi et al, 2012;Seidl, Lueken, Thomann, Geider, & Schröder, 2011). Secondly, research has pointed to the presence of overgeneralization of the autobiographical memory (Fromholt et al, 2003;Irish et al, 2011;Lemos et al, 2012;Martinelli et al, 2013), a phenomenon also observed in other psychopathological conditions as depression and suicidal attempts (e.g.…”
Section: Reminiscence and Autobiographical Memorymentioning
confidence: 99%
“…In contrast, deficits of personal semantics were related to the atrophy of anterior and posterior lateral temporal areas bilaterally, more pronounced on the left, as well as right frontal degeneration. More recently, Philippi et al (2012) reported positive correlations between hippocampal volume and episodic autobiographical memory for both recent and remote periods of life. Using the TEMPau task exploring autobiographical memory from three time periods (the last 5 years, middle age, teenage/childhood) and resting-state FDG-PET imaging, Eustache et al (2004) reported a temporal gradient of recalls in favor of remote past and that right hippocampal metabolism correlated uniquely with recent memories.…”
Section: Introductionmentioning
confidence: 99%